Effect of sulfate on chemically treated expansive clay - Nalbantoglu, Z. (Taylor & Francis Ltd, 2007)
Lime stabilization of clay soils has been widely used in highway and foundation layers as an economical method of providing a suitable pavement and fill material. However, it has been reported that the presence of sulfate is harmful in lime stabilized soils. The aim of this study is to focus on determining what sulfate level resulted in deleterious chemical reactions using lime stabilization. Laboratory tests were performed on both natural soil with no detectable sulfates and synthetic clay-lime-sulfate mixtures (artificial soils). Different amounts of sulfate were added to individual samples at concentrations of 0, 2000, 5000 and 10,000 parts per million (ppm). Laboratory investigation included the Atterberg limits, compaction, one dimensional swell and consolidation tests. The results of the laboratory tests indicated that sulfate content above 2000 ppm affected the volume change of the lime treated soils and an increase in the swell and compressibility of the soils was obtained.
International Conference on Advanced Characterisation of Pavement and Soil Engineering Materials -- JUN 20-22, 2007 -- Athens, GREECE